Bats of Southern and Central Africa : a biogeographic and taxonomic synthesis - Monadjem, Ara; Taylor, Peter John, 1963-; Cotterill, Fenton; Schoeman, M. Corrie (Wits University Press, 2020)
This revised edition supplements the original account of bat species found in Southern and Central Africa with eight newly described species, bringing the total to 124. Updates to information on their evolution, biogeography, ecology and echolocation are based on the latest original research and will be invaluable to students and scientists.